1990
DOI: 10.1037/0735-7028.21.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Differences in values between short-term and long-term therapists.

Abstract: We empirically examined Budman and Gurman's theoretical proposals concerning major differences in the value systems of long-vs. short-term therapists. Ss were 222 randomly selected licensed psychologists who indicated their preferred approach (short-term or long-term). Values were assessed with a scale designed for the study. Overall, results indicate that therapists who prefer a short-term approach are more likely to endorse the proposed values of the short-term therapist than are therapists who prefer a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In another training study, Levenson and Bolter (1988) examined the values and attitudes of psychiatry residents and psychology interns before and after a 6-month seminar and group supervision in TLDP. They found that after training there were significant changes in the students' attitudes (e.g., willingness to be more active) as measured by a questionnaire designed to highlight value differences between short-term and long-term therapists (Bolter, Levenson, & Alvarez, 1990). Other research has supported these findings (Neff, Lambert, Lunnen, Budman, & Levenson, 1997).…”
Section: Researchmentioning
confidence: 99%
“…In another training study, Levenson and Bolter (1988) examined the values and attitudes of psychiatry residents and psychology interns before and after a 6-month seminar and group supervision in TLDP. They found that after training there were significant changes in the students' attitudes (e.g., willingness to be more active) as measured by a questionnaire designed to highlight value differences between short-term and long-term therapists (Bolter, Levenson, & Alvarez, 1990). Other research has supported these findings (Neff, Lambert, Lunnen, Budman, & Levenson, 1997).…”
Section: Researchmentioning
confidence: 99%
“…The existence of these hypothesized, fundamental value differences between long and short-term counsellors was confirmed by Bolter et al (1990). In their research counsellors who stated they preferred a brief approach consistently endorsed the short-term counsellor values.…”
Section: The Values Of Planned Brief Counsellorsmentioning
confidence: 82%
“…Practitioner interest in brief therapeutic approaches has greatly increased and will most probably continue to increase over the years (Bolter, Levenson, & Alverez, 1990). A planned short-term therapy format for intervention appears to be both a viable and essential practice modality because health maintenance organizations and employee assistance programs generally favor highly structured brief forms of therapy (Wells, 1994).…”
Section: Resultsmentioning
confidence: 99%